2002
DOI: 10.1016/s1441-3582(02)70155-9
|View full text |Cite
|
Sign up to set email alerts
|

Purchase Loyalty is Polarised into Either Repertoire or Subscription Patterns

Abstract: We have observed that competitive repeat purchase markets are polarised into two radically different structures. The first and best known we call repertoire markets; these have few solely loyal buyers as most buyers allocate their category requirements across several brands in a steady fashion. The other we call subscription markets; these have many solely loyal buyers as most buyers allocate category requirements entirely to one brand. This is an empirical difference rather than a theoretical distinction, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 16 publications
4
110
1
1
Order By: Relevance
“…Some customers convert after a free trial but quit soon afterwards because of unresolved uncertainty or other reasons (Lewis, 2006). These wobblers -customers with a membership between trialers and members -might resemble first-time buyers in nonsubscription or repertoire markets (Blattberg, Thomas, & Getz, 2001;Sharp, Wright, & Goodhardt, 2002). Although the company had only a few wobblers (N=103), these wobblers might differ from trialers and members.…”
Section: Methodsmentioning
confidence: 99%
“…Some customers convert after a free trial but quit soon afterwards because of unresolved uncertainty or other reasons (Lewis, 2006). These wobblers -customers with a membership between trialers and members -might resemble first-time buyers in nonsubscription or repertoire markets (Blattberg, Thomas, & Getz, 2001;Sharp, Wright, & Goodhardt, 2002). Although the company had only a few wobblers (N=103), these wobblers might differ from trialers and members.…”
Section: Methodsmentioning
confidence: 99%
“…Many transactions are made and a non-contractual arrangement exists between the specifier (doctor) and seller (manufacturer). The prescription drug market is a repertoire market (Sharp, Wright, & Goodhardt, 2002) where doctors prescribe from a limited personal armamentarium of brands. This divided loyalty means that real brand switching is not easily distinguished from everyday shuffling within a doctor's armamentarium.…”
Section: Membership Of the Customer Basementioning
confidence: 99%
“…As observed (Sharp et al, 2002), the regularities in terms of loyalty shown in the frequently purchased consumer goods markets normally have meaning in those which have been called repertoire markets, so defined as to distinguish them from markets in which a subscription to a provider is required to purchase. The subscription, in fact, normally acts in limiting multi-brand purchasing, bringing it about that in these markets the brand loyalty metrics are usually higher.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 99%
“…As observed (Sharp & Wright, 2000;Sharp, Wright, & Goodhardt, 2002), the repertoire markets are those in which consumers hold personal repertoires of favoured brands amongst which they choose by frequently modifying their own buying preferences and which are therefore characterized by the presence of few customers who are 100% loyal to a specific brand. The subscription markets are in contrast those in which the clients must subscribe to a provider in order to make their purchases.…”
Section: Literature Review and Aims Of The Studymentioning
confidence: 93%